2000
DOI: 10.1063/1.1311393
|View full text |Cite
|
Sign up to set email alerts
|

Phonons and exciton recombination in CdSe/ZnSe self-assembled quantum dots

Abstract: We report resonant photoluminescence from CdSe/ZnSe self-assembled quantum dots. When CdSe quantum dots are resonantly excited, excitonic sharp micro-photoluminescence peaks originating from individual quantum dots are strongly enhanced in the region corresponding to optical phonon energies below the excitation. The phonons active in this process are identified as the longitudinal optical ͑LO͒ phonons from the CdSe dots, as the interface phonons, and tentatively as the LO phonons from the two-dimensional-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…Concerning the low temperatures, T€ urck et al [10] also observed a carrier feeding by means of a phonon-assisted tunneling from deep level states in the barrier into the quantum dots. Furthermore, our energy distance of 25 meV between the repeated energetic states is consistent with the observations of Rho et al [11]: They evaluated the LO-phonon energy to 27.3 meV in case of a CdSe quantum dot and to 23 meV for a 2D-like CdSe island.…”
Section: Resultssupporting
confidence: 79%
“…Concerning the low temperatures, T€ urck et al [10] also observed a carrier feeding by means of a phonon-assisted tunneling from deep level states in the barrier into the quantum dots. Furthermore, our energy distance of 25 meV between the repeated energetic states is consistent with the observations of Rho et al [11]: They evaluated the LO-phonon energy to 27.3 meV in case of a CdSe quantum dot and to 23 meV for a 2D-like CdSe island.…”
Section: Resultssupporting
confidence: 79%
“…This mechanism is similar to that used early to explain the disappearance of the narrow lines out of the -PL spectra. 5,23,27,44,50 The structure of the paper is as follows. In Sec.…”
Section: Introductionmentioning
confidence: 99%
“…The first and second longitudinal-optical (LO) phonon replicas are clearly defined. The energy difference adjacent pairs of 0LO-CdSe, 1LO-CdSe, and 2LO-CdSe is about 33 meV, which exceeds the LO phonon energy of bulk CdSe (25 meV) [17], because the compressive strain at the interface of CdTe and ZnSe increases the LO phonon energy [18]. However, when the coverage is increased to 5.0 MLs, the CdSe-precursor emission disappears.…”
Section: Methodsmentioning
confidence: 85%